The book of magic [large type] - Hoffman, Alice (Hoffman, Alice. Practical magic series, 2021)
"The Owens family has been cursed in matters of love for over three hundred years, but all of that is about to change. The novel begins in a library, the best place for a story to be conjured, when beloved aunt Jet Owens hears the deathwatch beetle and knows she has only seven days to live. Jet is not the only one in danger - the curse is already at work. A frantic attempt to save a young man's life spurs three generations of the Owens women, and one long-lost brother, to use their unusual gifts to break the curse as they travel from Paris to London to the English countryside where their ancestor Maria Owens first practiced the Unnamed Art. The younger generation discovers secrets that have been hidden from them in matters of both magic and love by Sally, their fiercely protective mother. As Kylie Owens uncovers the truth about who she is and what her own dark powers are, her aunt Franny comes to understand that she is ready to sacrifice everything for her family, and Sally Owens realizes that she is willing to give up everything for love"--